Analisis Pemahaman Konsep Matematis Siswa dalam Pemecahan Masalah Berdasarkan Teori APOS - Lapele, Dina Amalya; Buton, Iskandar; Sopamena, Patma (JRPM (Jurnal Review Pembelajaran Matematika), 2024)
This research discusses the student understanding of mathematical concepts in solving story problems based on APOS theory. The method used in this research is qualitative. The subjects were 3 students of class XI IPS-1. The subjects selected are subjects that have all the conceptual understanding indicators. The research instrument used was test questions and sheets interview. The data collection techniques were test, interviews and documentation. The data analysis techniques used were data reduction, data presentation and conclusions. The results of the study showed that 2 students fulfilled all stages of APOS perfectly, namely action, process, object and scheme. While 1 student only reached the action stage. The student was unable to reach the process, object and scheme stages. This is because the student only understands the concept verbally and does not understand the meaning of the concept of arithmetic sequences and series.